Peningkatan Motivasi Belajar Ips Melalui Metode Role Playing (Bermain Peran) Pada Siswa Kelas V Sdn Pabelan 01 Kartasura Sukoharjo Tahun 2012/ 2013 - Wijayanti, Rulis; , Drs. Rubino Rubiyanto, M.Pd (2017)
The purpose of this research is to increase the students' learning motivation in the social science learning using the strategy implementation and the active learning method of role playing of the 5th grade students in the first semester in SDN Pabelan 01 Kartasura in the academic year of 2012/2013. The research method used was the method of class research action. The research design was conducted through two cycles, starting from planning, action implementation, observation, reflection and continued with next cycle planning. This Class Research Action lasted from June 2013 up to July 2013 in which the subjects of research were the 5th grade students in the first semester in SDN Pabelan 01 Kartasura. The results of this Class Action Research were: 1) In the initial condition, the average amount of students who were diligent in doing the task was 50%, then in the cycle I, it increased into 64% and in the cycle II, it increased into 80%. Meanwhile, the average amount of students who were tough in solving the difficulties in the initial condition was 32%, then in the cycle I, it increased into 48%, and in the cycle II, it increased into 60%. 2) The amount of students who were motivated in the learning underwent and increase from the initial condition, the first cycle up to the second cycle. In the initial condition, the among of the motivated students was 40%, in the first cycle was 56% and in the cycle II was 68%. Based on the result findings of this research, it can be concluded that the learning method of role playing can be used to increase th learning motivation of Social Science in the 5th grade students of SDN Pabelan 01 Kartasura Sukoharjo in the academic year 0f 2012/2013.